Global Trend of Stunting in The Last Decade: A Bibliometric Analysis - Yohanis Ndapa Deda; Maria Paula Marla Nahak; Aplonia Pala (Amerta Nutrition)
Background: Stunting is a growth and development problem in children caused by chronic malnutrition and disease. There is no bibliometric analysis related to stunting globally and simultaneously using metadata from GS (Google Scholar) and Scopus on Vosviewer visualization from 2012 to 2022.